Empagliflozin rescues primary murine cardiac fibroblasts, but not cardiomyocytes, from hypoxia-reoxygenation injury through STAT3-mediated cascades. (3rd October 2022) - Mylonas, N; Efentakis, P; Nikolaou, P E; Zerikiotis, S; Pieper, M P; Dimitriadis, G; Iliodromitis, E K; Andreadou, I
Abstract: Introduction: Empagliflozin (EMPA) is a selective sodium glucose co-transporter 2 inhibitor (SGLT2i) and an established drug against type 2 diabetes mellitus. Cardiovascular clinical outcome trials on EMPA have shown a reduced mortality rate related to major cardiovascular events, but the precise mechanism of action remains elusive. We have previously proved that chronic EMPA administration reduces infarct size in an in vivo murine model of ischemia / reperfusion injury, irrespective of the diabetic status. The cardioprotective effect of EMPA was attributed to the increase of Signal Transducer and Activator of Transcription 3 (STAT3) phosphorylation. Purpose: In this study we aimed to decipher the cell specific effects of EMPA on primary adult ventricular murine cardiomyocytes (pAVMCs) and primary murine cardiac fibroblasts (pMCFs), subjected to hypoxia/reoxygenation (HYP/REO) and to 1) investigate the effect of EMPA on cell death, and 2) reveal the mechanism of cardioprotection. Methods: PAVMCs and pMCFs were isolated from adult C57BL/6 murine hearts (n=4–6) and were incubated with EMPA (500nM–100nM) for 24 hours. Cells were then subjected to 3 hours of HYP (99% N2), followed by 1 hour of REO. STATTIC, a selective STAT3 inhibitor was used (500nM–1μM) to determine the contribution of STAT3 on the observed effect. MTT assay was performed at the end of REO to determine cell viability. To unravel the mechanism of cardioprotection, the experimental protocol was repeated, and the cells were either stained with dihydroethidium (DHE) dye to determine relative oxidative stress changes or were harvested for isolation of total protein content. We focused on STAT3 and Akt kinase as key mediators of the cardioprotective survivor activating factor enhancement (SAFE) and the reperfusion injury salvage kinase (RISK) pathways. We also investigated the expression of Cardiotrophin-1 (CT-1), as a potential upstream mediator of STAT3 phosphorylation. Results: The evaluation of cell death revealed that pMCFs viability was significantly increased upon EMPA treatment. Added to this, STATTIC co-treatment with EMPA blunted the protective effect on pMCFs, which indicates that EMPA's protection is STAT3-mediated. Oxidative stress remained unaltered by the treatments. Investigation of the molecular pathways that are responsible for the increased viability of pMCFs revealed that EMPA treatment induces an increased phosphorylation of STAT3 and an increase in CT-1 expression, which are both reversed by STATTIC. Akt phosphorylation and expression remained unchanged by EMPA treatment. Notably, the effect of EMPA on pAVMCs' viability was negligible. Conclusion(s): EMPA does not protect pAVMCs, from HYP/REO injury. EMPA rescues the pMCFs in a STAT-3 dependent manner which indicates that EMPA's cardioprotective effect is cell specific and implicates the SAFE pathway. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boehringer Ingelheim International GmbHGrant title: "Investigation of the distinct effects of Empagliflozin on different cell populations of the healthy myocardium"